2019
DOI: 10.1093/biolinnean/blz190
|View full text |Cite
|
Sign up to set email alerts
|

The pelvis as an anatomical indicator for facultative bipedality and substrate use in lepidosaurs

Abstract: Facultative bipedality is regarded as an enigmatic middle ground in the evolution of obligate bipedality and is associated with high mechanical demands in extant lepidosaurs. Traits linked with this phenomenon are largely associated with the caudal end of the animal: hindlimbs and tail. The articulation of the pelvis with both of these structures suggests a morphofunctional role in the use of a facultative locomotor mode. Using a three-dimensional geometric morphometric approach, we examine the pelvic osteolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Studies on pelvic morphology in several other tetrapod groups contrast with our results for birds, with the pelvic shape of frogs, lepidosaurs, and some small‐to‐medium‐sized mammals being strongly associated with locomotor ecology (Álvarez et al, 2013; Grinham & Norman, 2020; Jorgensen & Reilly, 2013). Terrestrial carnivoran mammals follow a similar pattern as birds, in that their pelvic morphology is not significantly influenced by locomotor behavior (Lewton et al, 2020; Martín‐Serra et al, 2014).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Studies on pelvic morphology in several other tetrapod groups contrast with our results for birds, with the pelvic shape of frogs, lepidosaurs, and some small‐to‐medium‐sized mammals being strongly associated with locomotor ecology (Álvarez et al, 2013; Grinham & Norman, 2020; Jorgensen & Reilly, 2013). Terrestrial carnivoran mammals follow a similar pattern as birds, in that their pelvic morphology is not significantly influenced by locomotor behavior (Lewton et al, 2020; Martín‐Serra et al, 2014).…”
Section: Discussioncontrasting
confidence: 96%
“…Likely at least some role is played by ecological and physiological factors not fully captured by our functional categorization (e.g., egg size, see Shatkovska et al, 2018; and Abourachid et al, 2019; or respiratory action, see Baumel et al, 1990). It seems unlikely, however, that this fully explains the weak relationship between locomotor ecology and pelvic shape we found, given that our categories reflect major differences in life history and are similar to those used in studies on birds and other clades that have recovered stronger relationships (e.g., Anten‐Houston et al, 2017; Grinham & Norman 2020; Habib & Ruff 2008; Pigot et al 2020). Our chosen landmark configuration presumably also affected the results, but we believe that the general findings would have held under most alternative sets of landmarks encompassing the three‐dimensional pelvis as a whole.…”
Section: Discussionmentioning
confidence: 77%
“…What is the degree of quadrupedality in a facultative quadruped? While some recent studies have clarified these questions at more narrow phylogenetic scales (Grinham & Norman, 2020a , 2020b ), there are to our knowledge no quantitative studies to clarify this term across a broad sample and the literature lacks ethological case studies with temporal data. Of these ambiguous cases, hopping mammals (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Species that frequently occur both on trees or rocks (as adults) and on the ground were also classified as scansorial because we assume the agility of a gravid female would be most greatly constrained by any climbing activity or when trying to lodge itself in rock crevices (Schwarzkopf et al., 2010; Vitt, 1981). Semi‐aquatic species ( n = 75) were classified as scansorial if they are also semi‐arboreal or semi‐saxicolous (Grinham & Norman, 2020), or as terrestrial otherwise. A preliminary analysis showed semi‐aquatic species were not significantly different than either scansorial or terrestrial ones (not shown).…”
Section: Methodsmentioning
confidence: 99%